Comparison of transdermal fentanyl and oral tramadol for lateral thoracotomy in dogs: cardiovascular and behavioural data. (January 2019) - Read, Kate; Khatun, Mahmuda; Murphy, Helen
Abstract: Objective: To compare the analgesic efficacy and suitability of an existing oral tramadol-based protocol with a transdermal fentanyl-based protocol following lateral thoracotomy in dogs. Study design: Prospective randomized clinical trial. Animals: A group of 16 healthy laboratory beagle dogs. Methods: Dogs were randomly allocated to one of two treatment groups: group F (intramuscular methadone 0.2 mg kg –1 and transdermal fentanyl 2.6 mg kg –1 both administered on discontinuation of anaesthesia, n = 8) or group T (intramuscular methadone 0.2 mg kg –1 on discontinuation of anaesthesia and again 4 hours later, followed by oral tramadol 12 mg kg –1 per 24 hours commencing 7 hours after discontinuation of anaesthesia, n = 8). Intercostal bupivacaine (0.5–1 mg kg –1 ) and subcutaneous carprofen (4 mg kg –1 ) were administered to all dogs at induction. Body weight (BW), presence of clinical signs, pain score, activity, heart rate (HR) and mean arterial pressure (MAP) were assessed for 72 hours postoperatively. Results: No significant differences were observed in BW change, presence of clinical signs or gross locomotor activity between groups. Pain scores were low at all times for all dogs, and rescue analgesia was not required. Dogs in group T exhibited higher pedometric activity ( p = 0.006), HR ( p < 0.001) and MAP ( p < 0.001) than those in group F, in particular on night 1 following surgery. Least squared mean (LSM) pedometric activity was 1.81 and 1.02 jerks minute –1, LSM HR was 111.13 and 78.64 beats minute –1 and LSM MAP was 111.62 and 105.24 mmHg, respectively, in groups T and F. Conclusions and clinical relevance: Both regimes appear to provide adequate analgesia following lateral thoracotomy in dogs. Ease of administration of transdermal fentanyl compared to oral tramadol is advantageous. Reduced activity observed with the fentanyl regime was not associated with any adverse effects and may be desirable following some invasive surgeries. However, while transdermal fentanyl remains currently unavailable in the European Union, the oral tramadol-based regime provides an acceptable alternative.